The Influence of Adequate Transportation Infrastructure, Effective Logistics Management and Planning and the Use of Information Technology on Smooth Logistics - Andino Artha R; Muhammad Tohir (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The effect of Infrastruktur transportasi yang memadai, Manajemen dan perencanaan logistik yang efektif and Pemanfaatan teknologi informasi on Kelancaran Logistik is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Adequate transportation infrastructure has an effect on smooth logistics; 2) Effective logistics management and planning has an effect on smooth logistics; and 3) Utilization of information technology has an effect on smooth logistics.